Circulating DNA and frequency of colorectal cancer brain metastases in a presumed high-risk group - Louise Bach Callesen; Anders Kindberg Boysen; Rikke Fredslund Andersen; Rikke Beese Dalby; Karen-Lise Garm Spindler (Scientific Reports, 2023)
Abstract This explorative prospective observational pilot study investigated if suggested risk factors, rectal cancer and lung metastases, could add to a relevant detection rate of asymptomatic brain metastases (BM) from colorectal cancer (CRC). Secondary, prognostic biological aspects were investigated by translational analysis of plasma samples. The study enrolled patients with rectal cancer and lung metastases. At inclusion, patients underwent a standard MRI scan of the brain. Cell-free DNA (cfDNA) level was measured by a direct fluorescence assay (DFA), and circulating tumor DNA (ctDNA) by ddPCR. BM was detected in one of twenty-nine included patients. Patients had higher cfDNA levels than healthy subjects (p < 0.01). Patients with the primary tumor in situ had higher cfDNA levels than those with resected primary tumor (p < 0.01). Patients with liver involvement had higher cfDNA levels (p = 0.12) and circulating tumor DNA levels (p = 0.01) than those without liver involvement. In conclusion, the modest incidence of BM does not justify routine MRI of the brain in this selected population. cfDNA by DFA could be a valuable tool when planning treatment and follow-up for CRC patients. Future studies should focus on identifying further characteristics and biomarkers associated with a high risk of BM, enhancing the possibility for early intervention.